A tale of two crises: affective polarization in Greece - Nezi, Roula (Frontiers in Political Science, 2024)
Affective polarization, the strong feeling of animosity toward the supporters of the opposite party is rising in Europe. Several studies have examined the impact of ideological extremity and partisanship as a social identity on the rise of affective polarization. However, the impact of policy preferences on affective polarization remains relatively unexplored. I am at filling this gap by examining how preferences towards measures taken at addressing both the economic and the health crises impact affective polarization. Using newly collected data from Greece, a country with historically high levels of affective polarization, the analysis reveals that both policies have an impact of affective polarization but there are asymmetries on how policy preferences influence it. For the supporters of the governing conservative party, affective polarization appears to be policy-driven, whereas for the supporters of the opposition, the populist left-wing party SYRIZA, it is predominantly ideology-driven. Interestingly, the supporters of the governing party continue to align with the pro-memorandum stance even in the absence of an actual memorandum.